Fundamental Of Entrepreneurship (ENT300) : The U-Laife cafe business planning / Nurul Izzah Mohamad Elly … [et al.]. - Mohamad Elly, Nurul Izzah; Jamal, Nurhaliza; Was, Nur Azlin; Ahmad Nizam, Nur Ernaniza; Zinal Abidin, Nur Fatin Qirana (2019)
U-LAIFE cafe is a place where we sells buns, desserts and coffee and its a combination of cafe and bakery. It is located in UiTM Kota Samarahan, Campus 2. Our goal is to provide the students of UiTM with freshly brewed coffee and various types of desserts that they can choose from through their heart desire. Our cafe’s mission is to be UiTM’s students first choice. For a while, students of UiTM had to go to Summer Mall whenever they’re craving for coffee but with the existence of our cafe, we will become their first choice when they think of coffee. Meanwhile, the vision of our cafe is to sell affordable coffee and desserts which everyone can enjoy. We sells coffee and desserts with low prices so that every student can still satisfy their craving and does not need to worry about spending too much.